Tinjauan Hukum Perdata terhadap Perjanjian Kerja: Hak dan Kewajiban Pekerja serta Pengusaha - Andre Marten; Alvaro Anatollius Vivaldy Nonga (Media Hukum Indonesia (MHI), 2026)
This study examines the position of employment agreements within the civil law system and their relationship to labor law, focusing on the rights and obligations between workers and employers. Using normative legal research methods, this study analyzes relevant laws and legal doctrines. The results indicate that employment agreements, although based on the principle of freedom of contract (Article 1338 of the Civil Code), have a special character due to their subordinate nature, placing workers under the orders of employers. Therefore, freedom of contract in employment relationships is limited by labor law provisions to protect workers who have a weak bargaining position. Employment relationships give rise to reciprocal rights and obligations that must be implemented fairly, proportionally, and in good faith. Thus, employment agreements are not only legally binding but also serve as a means of realizing social justice and worker welfare.